Associations of time spent on homework or studying with nocturnal sleep behavior and depression symptoms in adolescents from Singapore - Sing Chen Yeo; Jacinda Tan; June C. Lo; Michael W.L. Chee; Joshua J. Gooley (2020)
To investigate associations of adolescents' time spent on homework/studying with nocturnal time for sleep and depression symptoms, in a competitive academic environment. Cross-sectional, anonymous survey of sleep habits, school life, and health-related measures. Eight schools in Singapore. Total 1225 adolescents aged 13–19 years. Self-reported sleep behavior and time use data were collected separately for school days and weekends. Multiple regression models were used to test covariation of time spent on homework/studying with other activities, and associations of homework/studying duration with depression symptoms. Time in bed for sleep and media use were inversely related with homework/studying duration on both school days and weekends, adjusting for time spent on other activities and demographic variables. Face-to-face family time and hanging out with friends were also reciprocally related with homework/studying duration on weekends. Depression scores were higher in adolescents who spent long hours on homework/studying. On school days, this was mediated by reduced time in bed for sleep. On weekends, homework/studying duration associated with depression symptoms, adjusting for time in bed and other covariates. Adolescents who spent ≥5 hours on homework/studying per day on weekends had greater symptoms of anhedonia and anxiety. In a competitive academic setting, adolescents who spent more time on homework/studying spent less time on sleep, media use, and social activities. Independent of effects on sleep, long hours on homework/studying on weekends may be a risk factor for depression. Reducing adolescents' workload outside of class may benefit their sleep, schoolwork-life balance, and mental well-being.